Effectiveness of tenofovir/emtricitabine versus zidovudine/lamivudine in combination with efavirenz in antiretro viral-naive HIV infected patients / Siti Mahanim Shaik Ismail - Shaik Ismail, Siti Mahanim (2015)
Durable suppression of replication of the human immunodeficiency virus (HIV) depends on the use of potent, well-tolerated antiretroviral regimens to which patients can easily adhere. Combination of two NRTIs and one NNRTI is the best first line regimen in treating retroviral disease (RVD) as compared to combinations of other groups. Tenofovir and Zidovudine are the two drugs that mostly use as one of NNRTIs in combination with either Lamivudine or Emtricitabine. Review of previous literature had shown that there were conflicting data on the superiority of either regime based on virologic and immunologic response. A local, retrospective observational cohort study was conducted to evaluate the virological response (primary endpoint), immunological response and the safety profile between TDF and AZT regimens. A total of 154 ART-nai've samples from HTAR and HSB were recruited. No statistically significant differences were observed in HIV RNA suppression at 24 weeks and 48 weeks (p = 0.407 and p = 0.521, respectively). Mean difference in CD4 increments were also not significant (p = 0.54, 95% CI -59.97, 31.83 at week 24; p = 0.68, 95% CI -51.41, 33.59 at week 48). However, AZT was found with more adverse events that leads to discontinuation (p-value <0.001). There were two cases of virological failure in TDF group but the association was not significant (p = 0.497). Only education level was identified as predictor of therapy effectiveness. Although there was no significant difference in virological and immunological responses, TDF still has advantage over AZT because of its better safety profile